Beyond skin deep: addressing comorbidities in psoriasis. Issue 11 (10th May 2020) - Kovitwanichkanont, Tom; Chong, Alvin H; Foley, Peter
Summary: Psoriasis is a chronic inflammatory disease that is commonly encountered in primary care and is associated with significant morbidity that extends beyond the skin manifestations. Psoriasis is associated with an elevated risk of psoriatic arthritis, cardiovascular disease, obesity, insulin resistance, mental health disorders, certain types of malignancy, inflammatory bowel disease and other immune‐related disorders, and hepatic and renal disease. Enhanced recognition of these comorbidities may lead to earlier diagnosis and potentially better overall health outcomes. Psoriatic nail involvement, severe skin disease and obesity are associated with a greater risk of psoriatic arthritis. Individuals with psoriasis should be routinely screened for psoriatic arthritis to allow for early intervention to improve long term prognosis. Life expectancy is reduced in people with psoriasis due to a variety of causes, with cardiovascular disease and malignancy being the most common aetiologies. Psoriasis affects several factors that contribute to worsened quality of life and increased risk of depression and anxiety. Effective therapies are now available that have been shown to concurrently improve skin disease, quality of life and psychiatric symptoms. As the concordance between psychosocial impact and objective disease severity does not always correlate, it is essential to tailor management strategies specifically to the needs of each individual. Cigarette smoking and excess alcohol consumption are among the most important modifiable risk factors that increase the likelihood of psoriasis development and severity of skin disease. This provides a compelling rationale for smoking cessation and limiting alcohol intake in people with psoriasis beyond their traditional harmful health consequences.